Potential Impurities of Tigecycline: Synthesis, Isolation, Characterization and In Vitro Pharmacological Evaluation - Sharavanan, Selliamman P. N.; Venkatesan, Chidambaram S.; Sathiyanarayanan, Singaram; Kabilan, Senthamaraikannan (Current Pharmaceutical Analysis, 2020)
Background: Tigecycline is a known antibiotic in the tetracycline family and a chemical analog of minocycline. It may be used for the treatment against drug-resistant bacteria. Methods: HPLC method was used for related substance analysis. The degraded impurities during the process were isolated and characterized by IR, HRMS (High Resolution Mass Spectrometry) and NMR spectral analysis. Result: Four impurities of tigecycline, a broad spectrum antibacterial agent, were identified, synthesized and characterized. The in vitro biological evaluation of the isolated compounds showed significant antimicrobial and antioxidant properties to that of tigecycline. Apart from these, the tigecycline drug substance showed significant degradation under oxidation conditions. Conclusion: The extensive investigational data confirm the structure of the four impurities. The specification limit for these impurities is applied based on the toxicological data. The antimicrobial activity revealed that the impurity 4 shows excellent activity towards both Gram-positive and Gram-negative bacteria when compared with tigecycline. The results obtained for DPPH (2,2-diphenyl-1- picrylhydrazyl) antioxidant activity concluded that the impurity 2 and the impurity 3 showed good antioxidant properties when compared with tigecycline. There was no activity observed on fungi for both isolated degradants as well as tigecycline.
Keywords: antioxidant activity